Is land consolidation policy a solution for rice production and agricultural transformation in Vietnam? - Manh Hung Do; Trung Thanh Nguyen; Ulrike Grote (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
Since the global food price crisis between 2007 and 2008, governments in developing countries such as Vietnam have paid more attention to food security issues. The government of Vietnam has issued policies to sustain rice land and imposed restrictions upon the transformation of rice land to ensure food security. Land consolidation is important to increase the economies of scale in farming, and understanding its determinants and effects is useful for policy-makers to support agricultural transformation. In this study, we investigate factors affecting the voluntary participation of rice growers in land consolidation and examine the impacts of this participation on crop production costs, poverty, and rural transformation. Our results show that land consolidation is driven by farming efficiency. It significantly decreases land preparation and harvest costs, increases farm income, and reduces poverty. We conclude that land consolidation should be promoted to facilitate the redistribution of farm land from farmers who want to leave agriculture to those who continue to work in agriculture. The redistribution of farmland promotes agricultural transformation by reallocating labor from farm to non-farm sectors.
Keywords: D01; O12; Q12; 330; Rural transformation; land fragmentation; non-farm income; poverty reduction; simultaneous regression